A Comprehensive Study on the Contribution of Motivation, Placement, and Career Development to Employee Performance - Slamet Riyadi; Sutianingsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
In the office of the Boyolali Regency Environment Agency, this study was carried out.  The purpose of this study is to analyze the relationship between employee performance at the Boyolali Regency Environmental Office and factors such as intrinsic motivation, job satisfaction, and opportunities for advancement.  A quantitative approach is utilized in this investigation.  Up to 260 people working for the Boyolali Regency Environmental Agency make up the population.  In this study, 260 respondents made up the sample, which was obtained using a complete sampling approach.  Data analysis was done using SPSS for Windows version 26, which aided with multiple linear regression analysis.  Workplace motivation, job placement, and career advancement all have a favorable and significant impact on employee performance, according to the study.  Inspiration at work, finding a job, and advancing one's career have.